Directives for Sharia Banking Financial Performance In Indonesia - Sunarsih, Uun; Firmansyah, Dede (UNIVERSITAS NEGERI SURABAYA, 2018)
This study aims to analyse the influence of Islamic ethical identity, board of commissioners, audit committee and external audit on the financial performance of sharia banking. This study uses secondary data obtained through the website of each sharia bank by using purposive sampling and obtained 7 sharia banking. The results show that only the board of commissioners has an effect on the financial performance, so the bigger the board of commissioner the greater the role in conducting supervision in sharia banking. The identity of Islamic ethics has no effect, as investors have different views on company performance measures. The audit committee has no effect because it can not perform its role to reduce the opportunistic nature of management. External audit has no effect because it is unable to guarantee that the audit process goes according to the procedure so that it is deemed unable to provide a high quality audit.